Penerapan Augmented Reality dalam Pengenalan Budidaya Burung Walet - Siregar, Yosua Arihta R. Sada; Tommy, Tommy; Budiman, Arief (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2024)
This is a new author guidelines and article template of information technology journal since year 2018 publication. Article should be started by Title of Article followed by Authors Name and Affiliation Address and abstract. This abstract section should be typed in Italic font and font size of 11 pt and number of words of 150-200. Special for the abstract section, please use normal margin. The single spacing should be used between lines in this article. If article is written in Indonesian, the abstract should be typed in Indonesian and English. Meanwhile, if article is written in English, the abstract should be typed in English only.The abstract should be typed as concise as possible and should be composed of: problem statement, method, scientific finding results, and short conclusion. The abstract should only be typed in one paragraph and one-column format. Keywords:author guidelines; infotmation technology; article template